ANALYSIS OF DANGEROUS PERMISSION TYPES THE MOBILE APPLICATIONS - Yangiboev Navruz Zufar ugli (Galaxy International Interdisciplinary Research Journal, 2024)
The research paper explores the risks associated with different types of permissions requested by mobile apps and comprehensively analyzes their implications. Also, by examining the various permissions required by mobile apps, the study sheds light on the security vulnerabilities and privacy issues faced by users. Through systematic assessment and categorization, the study identifies different levels of risk associated with different permission types, providing valuable insights for both developers and users. The research also aims to improve understanding of mobile app security practices and empower users to make informed decisions about app permissions. Ultimately, the article serves as an important resource for stakeholders seeking to mitigate risks and protect user privacy in the rapidly evolving mobile technology environment.